PENGUKURAN KINERJA DAN AKUNTABILITAS PENDIDIKAN - Sukatin, Sukatin; Nasution, Fitri (UIN Imam Bonjol Padang, 2021)
Measuring teacher performance is an important part of the educational management control process, both public and private education organizations. However, because the nature and characteristics of public education sector organizations differ from those of the private sector, such performance must be measured and reported in the form of a performance report. There are also differences in the emphasis and orientation of performance measurement. The objectives of the performance appraisal in the public sector are: Knowing the level of achievement of educational organizational goals, providing learning facilities for educational personnel, improving the performance of education personnel for the next period, providing systematic consideration in making decisions about giving rewards and punishments to educational personnel, motivating educational staff, creating accountability for educational organizations.